Pendampingan Pemanfaatan E-Commerce Sebagai Media Promosi Yudharta Advertising and Press - M. Imron Mas'ud (JPM: Jurnal Pengabdian Masyarakat, 2023)
Today's business competition requires every business actor to have e-commerce as a promotional or trade media so that it opens up a wide market share. This service aims to create e-commerce for Yudharta advertising and press as a media for sales promotion. The e-commerce that will be made is product sales from yudharta advertising and press including sales of ISBN books published by yudharta press. The service is carried out for one week, the implementation process is divided into three stages, namely the FDG process, gathering information, mentoring, and launching the program. The result of the dedication is the availability of e-commerce as a promotional media marketplace in increasing sales and opening up a wider market share